A biomarker-based biological age in UK Biobank: composition and prediction of mortality and hospital admissions - Chan, MS; Arnold, M; Offer, A; Hammami, I; Mafham, M; Armitage, J; Perera, R; Parish, S (Oxford University Press, 2021)
Background